2009
DOI: 10.1074/jbc.m109.034165
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Corepressor SMILE Recruits SIRT1 to Inhibit Nuclear Receptor Estrogen Receptor-related Receptor γ Transactivation

Abstract: SMILE (small heterodimer partner interacting leucine zipper protein) has been identified as a corepressor of the glucocorticoid receptor, constitutive androstane receptor, and hepatocyte nuclear factor 4␣. Here we show that SMILE also represses estrogen receptor-related receptor ␥ (ERR␥) transactivation. Knockdown of SMILE gene expression increases ERR␥ activity. SMILE directly interacts with ERR␥ in vitro and in vivo. Domain mapping analysis showed that SMILE binds to the AF2 domain of ERR␥. SMILE represses E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
74
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 53 publications
1
74
0
1
Order By: Relevance
“…Expression vectors for FLAG-ERR␣, HA-ERR␤, and FLAG-ERR␥ were described previously (30). The ERR response element (ERRE)-mutated mLIPIN1 promoter was generated via site-directed mutagenesis (Stratagene), and the construct was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression vectors for FLAG-ERR␣, HA-ERR␤, and FLAG-ERR␥ were described previously (30). The ERR response element (ERRE)-mutated mLIPIN1 promoter was generated via site-directed mutagenesis (Stratagene), and the construct was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…RNA Isolation and Analysis-Total RNAs were isolated from cell lines or primary hepatocytes using TRIzol reagent (Invitrogen), in accordance with the manufacturer's instructions, and semi-quantitative and real time quantitative PCR analysis were conducted using primers for ERR␣, ERR␥, LIPIN1, LIPIN2, SHP, PGC-1␣ and PDK4 as described previously (4,30,32). All data were normalized to ribosomal L32 expression.…”
Section: Methodsmentioning
confidence: 99%
“…SMILE has also been reported to function as a coactivator of activating transcription factor 4 or as a corepressor of host cell factor-binding transcription factor (13,14). Previously, we have reported that SMILE is a corepressor of the estrogen receptor-related receptor g, glucocorticoid receptor (GR), constitutive androstane receptor, hepatocyte nuclear factor 4a (HNF4a), and CREBH (15)(16)(17). A recent study demonstrated that SMILE activates tumor suppressor p53 and inhibits the function of bone morphogenetic protein 6 by interacting with Smads (18,19).…”
mentioning
confidence: 99%
“…1). In addition to HNF4a, other transcription factors interacting with SMILE, including ERRg, GR, CREBH, and/or FOXO1 (6)(7)(8), might mediate the inhibitory effects of insulin on gluconeogenic gene expression (9,11,12). To summarize, the article by Lee et al (5) demonstrates that the nuclear orphan receptor SMILE plays a large role in the homeostatic regulation of hepatic gluconeogenesis and that correction of its aberrant activity (possibly via pharmacological agents) represents a promising avenue for the therapy of metabolic disease.…”
mentioning
confidence: 99%
“…However, in this issue of Diabetes, Lee et al (5) dissect the role of the small heterodimer partnerinteracting leucine zipper protein (SMILE) in insulinmediated hepatic glucose metabolism. SMILE is a member of the CREB/ATF family of basic-region leucine zipper (bZIP) transcription factors and has been reported to function as a corepressor of nuclear receptor superfamily genes, including estrogen-related receptor g (ERRg), glucocorticoid receptor (GR), hepatocyte nuclear factor 4a (HNF4a), and cAMP-responsive element-binding protein H (CREBH) (6)(7)(8). In fact, ERRg, GR, HNF4a, and CREBH have all been implicated in upregulating gluconeogenic gene expression (9-12).…”
mentioning
confidence: 99%